MODEL OF DEMAND FOR MOVEMENT OF POPULATION OF SMALL TOWNS ROUTE PASSENGER TRANSPORT - and (Municipal economy of cities. Series: «Economy science», 2013)
An approach to form the route passenger transportation demand model in small towns, for which the results of the passenger flow tabular survey on route network are the basis.